Prevalence of anaemia and caregivers' knowledge, practice and attitude towards its prevention among under-fives in Zanzibar, Tanzania: A cross-sectional study - Arafat Hassan Khatib; Angelina A. Joho (Elsevier, 2022)
Background: The prevention of anaemia among under-fives is largely contributed by the caregiver's knowledge, attitude, and practice in the preparation of foods and feeding practices. This study aimed to determine the prevalence of anaemia and caregiver's knowledge, attitude, and practices towards its prevention among under-fives in Zanzibar. Methods: A hospital-based analytical cross-sectional study was conducted which included 594 caregivers and their under-fives from April to June 2020 in Zanzibar. Data were collected using an interviewer-administered questionnaire. Predictors of knowledge, attitude, and practice were determined using binary logistic regression. Multivariate analysis was done to control all other variables. SPSS version 23.0 was used to analyse the data. P-value < 0.05 was considered significant. Results: The overall prevalence of anaemia among under-fives was 69.1%, 43.8%, 22.9%, and 2.4% of the under-fives had mild, moderate, and severe anaemia, respectively. Caregivers' knowledge, attitude and practice were 36.7%, 43.4%, and 49.8%, respectively. Having low family income, receiving information from family members, and mass media were the predictors of low level knowledge (AOR = 0.54, 95% CI = 0.32 - 0.92, p = 0.022, AOR = 0.53, 95% CI = 0.32-0.90, p = 0.018, and AOR = 0.34, 95% CI = 0.15 - 0.76, p = 0.009, respectively). Living in rural part of North Pemba district had a protective effect against negative attitude (AOR = 0.37, 95% CI = 0.23-0.66, p = 0.000). Having more than four under-fives and receiving information from media were the predictors of reduced chance of caregivers' good practice (AOR = 0.51, 95% CI = 0.28 - 0.91, p = 0.024, AOR = 0.40, 95% CI = 0.17-0.96, p = 0.041, respectively). Conclusion: The prevalence of anaemia among under-fives in this study was quite high and alarming. This was reflected by low knowledge, attitude, and poor feeding practices. This study has shown that living in the rural area was associated with less chance of having good knowledge, a positive attitude, and good feeding practices for the prevention of anaemia. Emphasis should be made on raising the level of knowledge, attitude, and feeding practice, particularly for caregivers residing in rural areas.